(untitled) (Journal of Academic Research, 2026)
The environment that provides early childhood education outside the home plays a significant role in increasing the risk of disease transmission in the community. In this study, 205 swabs were collected from children’s toys from 13 nurseries and 14 kindergartens in both the public and private sectors. Fifteen bacterial species were isolated using direct isolation on appropriate media. The results showed that Gram-positive bacteria were predominant (51.8%), with Gram-negative bacteria comprising a smaller percentage (48.2%). Private kindergartens recorded the highest percentage of Gram-positive contamination (42.0%), while public kindergartens recorded the highest percentage of Gram-negative contamination (34%). Public nurseries exhibited higher rates of both Gram-positive and Gram-negative bacterial contamination than private nurseries. As for nurseries, public nurseries had the highest rates of contamination with both positive and negative bacteria compared to private nurseries. The most prevalent Gram-positive bacteria were Bacillus spp., followed by Staphylococci (coagulase-positive) and Staphylococci (coagulase-negative). The most pervasive Gram-negative bacteria were Pseudomonas spp., followed by Enterobacter cloacea. The isolated Staph. aureus bacteria were tested against several antibiotics, and the results indicated that the highest resistance rate was observed with the antibiotic cefoxitin (70.4%).